Pelatihan Manajemen Administrasi dan Keuangan di Desa Blimbing Gudo Jombang - Nur Fadilah; Siti Kalimah; Achmad Asfi Burhanuddin (LP3M IAIFA Kediri, 2020)
Pangabdian to the community is intended to provide guidance and training to the community in this area of economic activity, improving the economic level of the community, especially the middle and lower economic classes. This entrepreneurial training activity was held on January 11, 2020. Training materials are chosen according to the needs of the people in Blimbing Village who have the opportunity to make the village more resilient and advanced and make family life more prosperous in particular and the village community in general. Therefore, in Blimbing Village, Gudo Sub-District, Jombang held entrepreneurship training to improve the economic level of the community.